(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
To utilize MWCNTs as influential reinforcement in polymer composites, reasonable dispersion and a satisfactory interfacial bond between the MWCNTs and polymer matrix must be ensured. The chemical modification of carbon nanotube surface (CNTs) could enhance their chemical compatibility and dispersibility with the polymer matrix. In this study, polymer matrix composites reinforced by pristine MWCNT and MWCNT grafted PMMA (CNTPMMA) were prepared. A comparative study executed to analyze the impact of MWCNT dispersion on the mechanical and tribological performance of the resultant polymer nanocomposite coating. The results showed that the dispersion of carbon nanotubes in the base polymeric material was improved after being grafted with polymethyl meth acrylate chains, and thus improved their mechanical and tribological performance in the composite coatings.